2013
DOI: 10.1002/srin.201300045
|View full text |Cite
|
Sign up to set email alerts
|

Study on Inclusions in Wire Rod of Tire Cord Steel by Means of Electrolysis of Wire Rod

Abstract: The wire rod electrolysis is an extraction approach of inclusions in wire rod based on non-aqueous solution electrolysis, which can extract large-size inclusions (>20 mm) from F5.5 mm wire rod even about F0.22 mm cord wire. Analysis and study on large-size inclusions in tire cord steel from domestic and overseas steel plants were carried out by wire rod electrolysis, the study shows that the sizes of inclusions in wire rod of tire cord steel are far larger than those observed by metallographic microscope or sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Undeformable inclusions like hard high-Al 2 O 3 inclusions, MgO·Al 2 O 3 inclusions and some other high-melting-temperature brittle inclusions are also extremely detrimental to tire cord steel and saw wire steel drawability and service performance, because these inclusions are unlikely to elongate and likely to fracture during hot rolling and cold working [1]. As shown in Figure 15 [2,55], Al 2 O 3 inclusions were found on the drawing fracture of steel tire cord and saw wire. Thus, eliminating these inclusions or modifying them into deformable ones is of crucial importance for the production of these high-carbon steel products.…”
Section: Control Of Inclusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Undeformable inclusions like hard high-Al 2 O 3 inclusions, MgO·Al 2 O 3 inclusions and some other high-melting-temperature brittle inclusions are also extremely detrimental to tire cord steel and saw wire steel drawability and service performance, because these inclusions are unlikely to elongate and likely to fracture during hot rolling and cold working [1]. As shown in Figure 15 [2,55], Al 2 O 3 inclusions were found on the drawing fracture of steel tire cord and saw wire. Thus, eliminating these inclusions or modifying them into deformable ones is of crucial importance for the production of these high-carbon steel products.…”
Section: Control Of Inclusionsmentioning
confidence: 99%
“…Al 2 O 3 inclusions at center of drawing fracture obtained using SEM ( a ) steel tire cord and ( b ) saw wire. Adapted from [2,55]. …”
Section: Figurementioning
confidence: 99%
“…The wire breaking rate will be higher when it is close to the diameter of product due to the influence of various factors. However, cord wires always require highquality products, generally not more than one breakage per 100,000 m. 5 Wire breakage will seriously reduce the quality of product, and also increase the potential risk when the wire is put into use, for example, it may cause tire explodes, resulting in serious traffic accidents. 6 Therefore, wire breakage has been paid much attention in steel wire forming and manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the lifetime of wire is controlled by local singular stresses 6 and crack initiations 7 at the vicinity of inclusions. Previous researches have shown that the size and hardness of inclusions have a certain promotion effect on the generation of cracks and fractures of wire, 8,9 and the effect is more obvious especially in the larger sized inclusions 10 . In addition to inclusion size, the chemical composition is also an important factor in shortening the life of wire, 11 mainly because that inclusion composition and geometry can lead to the heterogeneous distribution of stress at the vicinity of the inclusion 12 .…”
Section: Introductionmentioning
confidence: 99%